VATIS update : ozone layer protection. Vol. 4, No. 134, Jan-Feb 2016 - UN.ESCAP; Asian and Pacific Centre for Transfer of Technology (APCTT) (UN.ESCAP. Asian and Pacific Centre for Transfer of Technology, 2016)
VATIS Update Ozone Layer Protection is published 6 times a year to keep the readers up to date of most of the relevant and latest technological developments and events in the field of Ozone Layer Protection. The Update is tailored to policy-makers, industries and technology transfer intermediaries. Highlights : Ozone hole one of the largest on record -- Maldives to ban HCFC gas imports -- Freezer with hydrocarbon refrigerant -- Drop-in replacement for trichloroethylene -- Water mist extinguishers for spacecrafts -- Environmentally friendly chemical blowing agent -- Fumigation for postharvest pest control THE SCIENCE OF OZONE LAYER . 4 -- Ozone hole one of the largest on record -- NASA’s next ozone layer instrument -- More intense tropical cyclones without Montreal Protocol -- Ozone hole stretches wider -- Ozone depletion in the Arctic ODS PHASE-OUT IN INDIA . 6 -- Solar-powered ACs with IIT-Madras help -- Workshops on adsorption chillers IN THE NEWS . 7 -- Philippines to phase-out HCFCs -- Maldives to ban HCFC gas imports -- Afghanistan to prevent ozone depletion -- Russia set new directives for ODS production -- Global foam blowing agents market -- Refrigerator of the future REFRIGERATION/AIR-CONDITIONING . 9 -- Freezer with hydrocarbon refrigerant -- R290 compressor -- Chiller using new R410A replacement -- New refrigerant boosts energy efficiency -- Solar energy cooling system -- Cleaner and safer heat pumps SOLVENTS . 11 -- Bio-based cleaner -- Drop-in replacement for trichloroethylene -- Bio-based solvent technology -- VOC-compliant alternative solvent -- Solvent recycling systems -- Bio-based organic cleaner HALONS . 13 -- Water mist extinguishers for spacecrafts -- Water mist firefighting systems -- Targeted fire-fighting mist jet -- Twin-fluid hybrid fire suppression -- Oxygen reduction to extinguish fire FOAMS . 15 -- Environmentally friendly chemical blowing agent -- New foam expansion agents -- Liquid foam blowing agent FUMIGANTS . 16 -- Irradiation preserves blueberry, grape quality -- Fumigation ...